Padrões do uso do tempo por bezerras recebendo ou não suplemento em pastagem de azevém - Hampel, Viviane da Silva (2014)
The experiment was carried out to evaluate the time pattern is used by heifers, at two phenological stages of ryegrass (Lolium multiflorum Lam.), in four daily shifts. Heifers remained exclusively on pasture or grazing and receiving a supplement (oats or corn grain), in the proportion of 0.93% of body weight. Supplements were fed at 14 o'clock, Monday to Saturday. The grazing was continuous with a variable number of animals. The experimental design was completely randomized in a sub-subdivided plots arrangement. Ingestive behavior was assessed by 24 hours of visual observation, in four evaluation dates: two in the vegetative stage and two in the reproductive stage. Grazing time, ruminating and other activities, the number, duration and interval between meals were studied. Heifers receiving supplement remain less time at feeding station and perform fewer bites daily. In the reproductive stage of the ryegrass supplemented heifers stay longer in other activities. The grazing time of heifers receiving supplement is lower in the morning shift and in the night shift. The duration of the meals is lower at night, when the heifers receive supplement. The pattern of time use of the heifers is altered by receiving supplement and the change of the structural and qualitative characteristics of ryegrass during the phenological growth stages.